Attack Rate, Case Fatality Rate and Predictors of Pertussis Outbreak During Pertussis Outbreak Investigation in Ethiopia: Systematic Review and Meta-Analysis - Mengistie Kassahun Tariku; Abebe Habtamu Belete; Daniel Tarekegn Worede; Simachew Animen Bante; Agumas Alemu Alehegn; Biniam Kebede Assen; Bantayehu Addis Tegegne; Sewnet Wongiel Misikir (Springer, 2024)
Abstract Background Pertussis, a highly contagious, vaccine-preventable respiratory infection caused by Bordetella pertussis, is a leading global public health issue. Ethiopia is currently conducting multiple pertussis outbreak investigations, but there is a lack of comprehensive information on attack rate, case fatality rate, and infection predictors. This study aimed to measure attack rates, case fatality rates, and factors associated with pertussis outbreak. Methods This study conducted a systematic review and meta-analysis of published and unpublished studies on pertussis outbreaks in Ethiopia from 2009 to 2023, using observational study designs, using the guideline Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The study utilized databases like Science Direct, MEDLINE/PubMed, African Journals Online, Google Scholar and registers. The data were collected using an Excel Spreadsheet and then exported to STATA version 17 for analysis. Subgroup analysis was conducted to identify potential disparities. A random effects model was used to consider heterogeneity among studies. I2-squared test statistics were used to assess heterogeneity. The attack rate, case fatality rate, and odds ratio (OR) were presented using forest plots with a 95% confidence interval. Egger's and Begg's tests were used to evaluate the publication bias. Results Seven pertussis outbreak investigations with a total of 2824 cases and 18 deaths were incorporated. The pooled attack and case fatality rates were 10.78 (95% CI: 8.1-13.5) per 1000 population and 0.8% (95% CI: 0.01-1.58%), respectively. The highest and lowest attack rates were in Oromia (5.57 per 1000 population and in the Amhara region (2.61 per 1000 population), respectively. Predictor of pertussis outbreak were being unvaccinated [odds ratio (OR) = 3.05, 95% CI: 1.83-4.27] and contact history [OR = 3.44, 95% CI: 1.69-5.19]. Conclusion Higher and notable variations in attack and case fatality rates were reported. Being unvaccinated and having contact history were the predictors of contracting pertussis disease in Ethiopia. Enhancing routine vaccination and contact tracing efforts should be strengthened.